Health-Related Quality of Life in Elderly Patients With Pressure Ulcers in Different Care Settings. Issue 4 (July 2015) - Sebba Tosta de Souza, Diba Maria; Veiga, Daniela Francescato; Santos, Ivan Dunshee de Abranches Oliveira; Abla, Luiz Eduardo Felipe; Juliano, Yara; Ferreira, Lydia Masako
Abstract : PURPOSE: The purpose of this study was to measure and compare health-related quality of life in elderly patients with pressure ulcers in different health care settings (home care acute care facility, and long-term care facility [LTCF]). DESIGN: Cross-sectional comparative study. SUBJECTS AND SETTING: One hundred ten elderly patients with (n = 36) and without (n = 74) pressure ulcers living in LTCFs, hospitals, or at home. The research setting included 1 tertiary and 2 community-based hospitals, 10 LTCFs, and 18 community health centers in Brazil. METHODS: The Mini-Mental State Examination, Braden Scale for Predicting Pressure Sore Risk, and Medical Outcomes Study 36-Item Short Form Health Survey (SF-36) were used to assess cognitive status, pressure ulcer risk, and health-related quality of life, respectively. RESULTS: Compared with those without pressure ulcers, elderly patients with pressure ulcers reported significantly lower (worse) SF-36 scores on physical functioning ( P < .001) and role physical ( P < .05) in all settings, and on social functioning ( P = .045) and role emotional ( P = .036) in LTCFs. Subjects in hospitals with pressure ulcers scored significantly higher (better) SF-36 scores on mental health ( P = .046) and vitality ( P = .009). Hospitalized patients without pressure ulcers had lower SF-36 scores on bodily pain ( P = .007) and general health ( P = .026) than those living in LTCFs or at home. Patients without pressure ulcers in LTCFs had significantly lower Mini-Mental State Examination scores (lower cognitive status) than those living in other settings ( P = .001). CONCLUSIONS: Elderly patients with pressure ulcers who were hospitalized and living at home or in LTCFs reported low scores on physical functioning and role physical, and LTCF residents also reported low scores on social functioning and role emotional. This shows the need for an environment that includes health care professionals prepared to implement strategies for pressure ulcer prevention.